Determinants of Treatment Adherence among Patients with Severe Mental Disorders at the Kedungmundu Primary Health Center in Semarang City - Deviani Saskia Putri; Ayun Sriatmi; Eka Yunila Fatmasari (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2020)
Background: Treatment adherence among patients with severe mental disorders is needed to avoid drop-outs, relapses, and shackling. Kedungmundu Primary Health Center in Semarang City is known to have a low treatment adherence to patients with severe mental disorders. This study aimed to determine the factors associated with treatment adherence among patients with severe mental disorders.Methods: A quantitative study with a cross-sectional approach. The samples were 73 patients with severe mental disorders at The Kedungmundu Primary Health Center. Data were collected using questionnaires and analyzed using frequency distribution analysis and Spearman Rank Correlation Test.Results: The results indicated that knowledge (p = 0,000; r = 0,715), attitudes (p = 0,000; r = 0,839), family support (p = 0,000; r = 0,427), assessment of health workers (p = 0,000; r = 0,456), and the need for health services (p = 0,000; r = 0,716) have a positive correlation with treatment adherence among severe mental disorders patients.Conclusion: Kedungmundu Primary Health Center is suggested to provide psychoeducation to patients and families, improve the implementation of mental health programs, and empower mental health cadres.